2022
DOI: 10.1002/ca.23983
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the uterine artery: A meta‐analysis with implications for gynecological procedures

Abstract: The uterine artery (UA) is an arterial branch of the internal iliac artery in women, usually arising from the anterior division of the internal iliac artery. However, due to the high variability in the anatomy of the UA, embolization of this vessel may be challenging. Therefore, the objective of this meta‐analysis was to provide physicians with transparent data on the anatomy of the UA, using the available data in the literature. Databases such as PubMed, Scopus, Embase, Web of Science, and Google Scholar were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, embolization of the said vessel may be challenging due to its variable anatomy. Therefore, Ostrowski et al [16] analysed the complete anatomy of this artery In the study, it was stated that the knowledge about the morphometric values of the uterine artery (UTA) specifically its diameter is of great importance when choosing an appropriately-sized catheter for embolization procedures. The meta-analysis showed that the mean diameter of the uterine artery was 2.74 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, embolization of the said vessel may be challenging due to its variable anatomy. Therefore, Ostrowski et al [16] analysed the complete anatomy of this artery In the study, it was stated that the knowledge about the morphometric values of the uterine artery (UTA) specifically its diameter is of great importance when choosing an appropriately-sized catheter for embolization procedures. The meta-analysis showed that the mean diameter of the uterine artery was 2.74 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant lack of data regarding the variable anatomy of the IGA. The arterial anatomy of the pelvis is known for being highly variable, making it a difficult area to operate in [12,16,26,27]. The origin of the IGA has not been sufficiently studied in the past, even though its highly relevant in embolization procedures for pseudoaneurysms [13].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative followup gynecological examination and uterine ultrasound showed no uterine and pelvic abnormalities. Ligation of ascending branch of uterine artery combined with ligation of communicating branch of utero-ovarian artery was applied to enucleation of uterine broids after cesarean section in 4 cases.Uterine broids,which are the most common pelvic tumors in women, their blood supply almost exclusively originate from the uterine artery [11] .This operation was performed before myomectomy, which not only reduced intraoperative hemorrhage, but also shortened operation time [19] . It is an effective method to reduce the clinical recurrence rate and improve the success rate of intraoperative hemostasis [20] .…”
Section: Discussionmentioning
confidence: 99%
“…The arterial anatomy of the pelvis is quite variable [ 9 , 19 21 ]. This variability was showcased in a recent meta-analysis [ 13 ], which examined the origin and morphometric properties of the UA. Although the major anatomical textbooks describe the UA’s origin as being from the anterior trunk of the internal iliac artery, many other origins have been presented in the literature.…”
Section: Introductionmentioning
confidence: 99%